Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1016/j.tust.2015.10.040
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of fibers in SFRC segments for tunnel linings

Abstract: This paper presents research results regarding the distribution of steel fibers in concrete used to build precast tunnel segments for Line 9 of the Barcelona Metro. The fiber distribution was studied using the actual fiber contents obtained by means of crushed cores drilled from different points of three full-scale tunnel lining segments. A statistical analysis determined that the fiber content in the ends of segments tend to be greater than in the central zone. In addition, cores with a diameter of 150 mm wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 29 publications
(30 reference statements)
0
7
0
Order By: Relevance
“…Politècnica de Catalunya (UPC) inBarcelona, Spain, and Universidad Federico Santa Maria (UTFSM) in Valparaiso, Chile. These experimental programs were reported inMolins et al (2008),Monsó (2011),Aire et al (2015) andCarmona (2016).According to the latter, seven different types of concrete were included in this research: two conventional concretes (C) with compressive strength of 30 MPa and 50 MPa and reinforced with 30 kg/m 3 and 50 kg/m 3 of fibers respectively; two self compacting concretes with normal and high compressive strength, designated as SCC -N and SCC-H respectively, both reinforced with two fiber amounts 20 kg/m 3 and 40 kg/m 3 ; a third self compacting concrete of normal strength (designated as M series) reinforced with 30 kg/m 3 of four different type of fibers with different length (lf) and diameter (df), and almost identical aspect ratio (λf = lf/df). Finally, a sprayed concrete designed to be used as lining in mining tunnels, designated as SH and reinforced with and 40 kg/m 3 of fibers.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…Politècnica de Catalunya (UPC) inBarcelona, Spain, and Universidad Federico Santa Maria (UTFSM) in Valparaiso, Chile. These experimental programs were reported inMolins et al (2008),Monsó (2011),Aire et al (2015) andCarmona (2016).According to the latter, seven different types of concrete were included in this research: two conventional concretes (C) with compressive strength of 30 MPa and 50 MPa and reinforced with 30 kg/m 3 and 50 kg/m 3 of fibers respectively; two self compacting concretes with normal and high compressive strength, designated as SCC -N and SCC-H respectively, both reinforced with two fiber amounts 20 kg/m 3 and 40 kg/m 3 ; a third self compacting concrete of normal strength (designated as M series) reinforced with 30 kg/m 3 of four different type of fibers with different length (lf) and diameter (df), and almost identical aspect ratio (λf = lf/df). Finally, a sprayed concrete designed to be used as lining in mining tunnels, designated as SH and reinforced with and 40 kg/m 3 of fibers.…”
mentioning
confidence: 76%
“…Due to its simplicity and greater knowledge of the response of the FRC subjected to the BCN test, supported by a large number of researches both at the experimental level (Carmona et al, 2013;Aire et al, 2015) and numerical (Pros et al, 2011;2012;Pujadas et al, 2013), the BCN test is progressively being used to evaluate the post-cracking behavior of FRC (Chao et al, 2012;Kim et al, 2015;Carmona et al, 2016). It has also been used as a control test for fiber-reinforced shotcrete in several large projects, such as the Lima Metro (Geocontrol, 2015), the Chuquicamata Subterránea project of the Codelco -Chile mining company , and linings for 22.5 km tunnel of Follo Line in Norway.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of fibres in concrete develops the stress transfer mechanism by bridging cracks [ 9 ]. Due to good physical and mechanical parameters of SFRC it is applied for making various structural elements such as foundation slabs [ 10 ], bridge slabs [ 11 ], industrial floors [ 12 ], columns [ 13 , 14 ] or tunnel elements [ 15 , 16 , 17 , 18 ]. In SFRC production waste materials can also be applied [ 19 ] bearing in mind sustainable development of construction industry.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies on the mechanical properties of steel fiber-reinforced concrete (SFRC) linings and precast segments have shown that the randomness of fiber distribution manifests a good crack control capability [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%